Multiport energy gateway. Issue 10 (29th May 2019) - Tran, Yan‐Kim; Freijedo, Francisco D.; Dujic, Drazen
Abstract : Medium‐voltage‐direct‐current collection and distribution grids are being considered for emerging applications, and require enabling power electronic technologies. Medium‐voltage high power DC–DC converters are one of the solutions that will play an important role in future energy systems. This study presents a novel bidirectional multiport power electronic converter, interfacing medium‐voltage and low‐voltage distribution grids while integrating distributed energy storage elements, such as batteries and super‐capacitors. The multiport energy gateway concept is based on a modular input‐series output‐parallel topology includes medium frequency transformer for the galvanic isolation, and combines open‐loop and closed‐loop operated converter stages. Comprehensive converter design aspects and operating principles are presented and discussed considering representative cases of studies. The validity of the approaches is proved by simulation and experimental results obtained on a small scale prototype.